Postpartum Independent Recovery at Home by Utilizing the Yard as a Means of Providing Medicinal Plant: Pemulihan Mandiri Pascapersalinan di Rumah Dengan Memanfaatkan Pekarangan Sebagai Sarana Penyediaan Tanaman Obat - Sari Widyaningsih; Juanda Syafitasari; Edi Susilo; Parwito; Popy Siska Putri (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The main problems faced by postpartum women in Padang Pelawi Village include a lack of knowledge and access to appropriate health care methods, both physically and psychologically. Many postpartum women experience difficulties in breastfeeding, self-care after childbirth, and maintaining psychological balance. This empowerment activity seeks to increase community awareness and attitudes towards importance of postpartum maternal health care, as well as support postpartum mothers to avoid physical and psychosocial problems. Farmer women's groups in the village are empowered can make use of their yards by cultivating therapeutic plants that benefit postpartum women's recovery. The methods are socialization, training, technology application, evaluation and mentoring, and program sustainability. The community service program results showed an increase in the knowledge of women farmer groups in Padang Pelawi village. It is anticipated to have a lasting effect, and there is a need for continuous assistance for farm women groups in utilizing the yard and making ginger powder.